2018
DOI: 10.2166/wst.2018.343
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of chitosan/Fe2O3 nano composite for the adsorption of thorium (IV) ion from aqueous solution

Abstract: In this study, novel chitosan/FeOnano composite Ch/Fe-O was synthesized and evaluated as an adsorbent for removing thorium (IV) (Th) ion from aqueous solution. The Ch/Fe-O was characterized by X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET), Fourier transform infrared (FTIR) and scanning electron microscopy (SEM). Response surface methodology (RSM) was used in the optimization of Th adsorption for parameters such as pH, the initial metal ion concentration (Th concentration) and contact time. The statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
3
5
0
2
Order By: Relevance
“…This result approved with Keshvardoostchokami et al (2017) who used chitosan/ Fe 2 O 3 nanocomposite in removal of nickel, cadmium and lead from aqueous solution. The prepared HCS NC in our study adsorbs toxic ions in the order Pb(II) > Cd(II) > Cu(II) which is in agreement with Broujeni et al, 2018.…”
Section: Effect Of Contact Timesupporting
confidence: 86%
“…This result approved with Keshvardoostchokami et al (2017) who used chitosan/ Fe 2 O 3 nanocomposite in removal of nickel, cadmium and lead from aqueous solution. The prepared HCS NC in our study adsorbs toxic ions in the order Pb(II) > Cd(II) > Cu(II) which is in agreement with Broujeni et al, 2018.…”
Section: Effect Of Contact Timesupporting
confidence: 86%
“…The previously diagnosed bumps are completely covered, and more masses are dispersed onto the C-Fe2O3 surface, which denotes the existence of AB113 dye molecules on the C-Fe2O3 surface. Similar results relevant to the AFM analysis in the present study have been presented in previous works (Broujeni et al, 2018;Kyzas et al, 2013). The TGA graph of chitosan and C-Fe2O3 is presented in Fig.…”
Section: = (7)supporting
confidence: 91%
“…In addition, the pore volume and mean diameter are 0.286 cm 3 /g and 17.2 nm, respectively. Compared with the documented surface area value for a sample of pure chitosan (91.4 m 2 /g) (Broujeni et al, 2018), it can be concluded that the coating of chitosan with Fe2O3 significantly enhances the surface area of this polymer. Notably, solid materials with a large surface area are favorable as adsorbents in adsorption treatment systems, as this parameter reflects the number of adsorption sites for pollutant molecules.…”
Section: Characterization Analysesmentioning
confidence: 82%
See 2 more Smart Citations